Key success factors in digital transformation: fundamentals developed from a bibliometric analysis - Medved, Tilen; Kern, Tomaž; Krhač Andrašec, Eva (Serbian Journal of Management, 2025)
The article analyses a multidimensional digital transformation process. Digital transformation is a change or shift in operational and strategic frameworks necessitated by the rapid advancement of digital technology. Digital transformation is more than the implementation of advanced technology, it requires a cultural shift towards constant experimentation and openness to failure. Such changes make the organization agile, efficient, and customer-orientated, with the ability to quickly integrate new, comprehensive data into the entire decision-making and innovation process. The purpose of the research was therefore to analyse the most important success factors in digital transformation. The analysis serves as a basis for further theoretical research in this field and for practical implementation in organisational systems. As part of this research, a bibliometric analysis was carried out using the open-source tool VOSviewer. The analysis shows that digital transformation is particularly relevant in the fields of Computer Science; Business, Management and Accounting; and Engineering, namely in Germany, China and the Russian Federation. We have come to the conclusion that the key success factors in digital transformation are as follows: corporate organization and technology, collaboration and cultural change, holistic strategy, leadership and organizational structure, continuous learning and conformity to best practises.
Keywords: Digital transformation; Advanced technologies; Key success factors; Bibliometric analysis; VOSviewer